Association between vaspin rs2236242 gene polymorphism and atherosclerosis in ischemic stroke patients with diabetes mellitus in the Indonesian population - Danuaji, Rivan; Suroto; Purwanto, Bambang; Indarto, Dono; Muhammad, Faizal; Mirawati, Diah Kurnia; Widyaningsih, Vitri; Soetrisno; Subandi; Budianto, Pepi; Hambarsari, Yetty; Hamidi, Baarid Luqman; Prabaningtyas, Hanindia Riani; Hutabarat, Ervina Arta Jayanti; Ristinawati, Ira; Tejomukti, Teddy; Tedjo, Raden Andi Ario (Medical Journal of Indonesia, 2024)
BACKGROUND Stroke is the third leading cause of morbidity and second in mortality worldwide. Diabetes mellitus (DM) is a risk factor for stroke. Vaspin and single nucleotide polymorphism (SNP) rs2236242 involved DM pathogenesis. This study aimed to explore the correlation between SNP rs2236242, serum vaspin levels, and atherosclerosis in patients with ischemic stroke and DM. METHODS This study was conducted in Dr. Moewardi Hospital from 2022 to 2023. The case group included patients with ischemic stroke and DM, while the controls were those with ischemic stroke only. Tetra-primer amplification refractory mutation system-polymerase chain reaction was used to determine the genotypes. RESULTS There were 31 cases and 33 control. SNP rs2236242 showed that odds ratio (OR) (95% confidence interval [CI]) for AA-TT was 0.273 (0.241–0.305) and for TA-TT was 0.315 (0.298–0.341). The OR (95% CI) for allele A to T was 0.789 (0.373−1.669). The mean (standard deviation) serum vaspin level in the case group compared to the control was 1,570 (2,108) ng/ml versus 1,630 (1,428) ng/ml (p = 0.064). Higher vaspin levels were found in T allele of the TT (1,523 [2,269] ng/ml, p = 0.021) and TA (1,760 [1,349] ng/ml, p = 0.004) genotype groups than the A allele of the AA genotype group (0.914 [0.329] ng/ml). CONCLUSIONS Vaspin gene polymorphism AA genotype or A allele significantly reduces vaspin levels in patients with ischemic stroke with DM.